The Influence Of Total Quality Management (TQM) On Operational Performance Mediated By Innovation; Study On Msms Under The Guidance Of The MSME Incubator In Makassar City - Mahyuddin; Okta Nofri; S. Widad Ahmad (International Journal of Education Management and Religion, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Makassar City face various challenges that hinder their competitiveness both locally and globally. The main obstacles include low understanding of digital technology, limited access to capital, inadequate financial literacy, and weak managerial capabilities. In addition, inconsistent product quality and a lack of innovation make MSMEs vulnerable to market pressures, especially from imported products marketed through socio-commerce platforms such as TikTok Shop. To address these challenges, MSMEs need to adopt a comprehensive total quality management approach and enhance innovation as efforts to strengthen their operational performance. This study employs a quantitative method with an associative approach. The sample consists of 130 respondents from MSMEs under the guidance of the Makassar City MSME Incubator, selected using purposive sampling techniques. Data were collected through questionnaires designed with a Likert scale. The data were analyzed using the Structural Equation Modelling (SEM) method based on Partial Least Square (PLS), which includes the evaluation of the outer model, inner model, and goodness of fit to test the relationships among variables. The results show that Total Quality Management (TQM) has a positive and significant effect on innovation and operational performance. Innovation also positively influences the operational performance of MSMEs. Furthermore, innovation is proven to play a significant partial mediating role in the relationship between TQM and operational performance. These findings emphasize that the effective implementation of TQM, along with strong support for innovation, can enhance the competitiveness and sustainability of MSMEs in Makassar City.